Clostridium ramosum regulates enterochromaffin cell development and serotonin release - Mandić, Ana D.; Woting, Anni; Jaenicke, Tina; Sander, Anika; Sabrowski, Wiebke; Rolle-Kampcyk, Ulrike; von Bergen, Martin; Blaut, Michael (Scientific reports, 2019)
Peripheral serotonin (5-hydroxytryptamine: 5-HT) synthesized in the intestine by enterochromaffin cells (ECs), plays an important role in the regulation of peristaltic of the gut, epithelial secretion and promotes the development and maintenance of the enteric neurons. Recent studies showed that the indigenous gut microbiota modulates 5-HT signalling and that ECs use sensory receptors to detect dietary and microbiota-derived signals from the lumen to subsequently transduce the information to the nervous system. We hypothesized that Clostridium ramosum by increasing gut 5-HT availability consequently contributes to high-fat diet-induced obesity. Using germ-free mice and mice monoassociated with C . ramosum , intestinal cell lines and mouse organoids, we demonstrated that bacterial cell components stimulate host 5-HT secretion and program the differentiation of colonic intestinal stem progenitors toward the secretory 5-HT-producing lineage. An elevated 5-HT level regulates the expression of major proteins involved in intestinal fatty acid absorption in vitro , suggesting that the presence of C . ramosum in the gut promotes 5-HT secretion and thereby could facilitates intestinal lipid absorption and the development of obesity.